Hormone receptor-positive, HER2-negative, metastatic breast cancer responded well to abemaciclib and exemestane after palbociclib and fulvestrant failure: A case report and literature review - Mao, Yan; Lv, Meng; Wang, Yongmei; Cao, Weihong; Li, Wenfeng (Frontiers in Oncology, 2023)
There is uncertainty regarding the usefulness of CDK4/6 inhibitor based therapy for hormone receptor positive (HR+), human epidermal grow factor receptor 2 negative (HER2-), metastatic breast cancer(MBC), when CDK4/6 inhibitor treatment had previously failed. Furthermore, a biomarker for abemaciclib resistance has not been identified. Herein, we reported outcomes for a HR+/HER2- MBC patient diagnosed with multiple myeloma and treated with abemaciclib and exemestane, who had cancer progression after treatment with palbociclib and fulvestrant. Thalidomide was used in conjunction with all treatments. The patient had a good response to abemaciclib and exemestane, with progression-free survival much longer than previously reported. PI3KCA and TP53 mutations were identified after cancer progression following abemaciclib treatment. It is unclear whether thalidomide increased the effectiveness of abemaciclib. Whether benefit can be derived by the use of PI3K inhibitors, after cancer progression, requires further investigation and this may be best accomplished by use of next-generation sequencing.